A scoping review of cerebral reperfusion therapies in childhood and adolescence with arterial ischemic stroke - Ana Lúcia de Paula Garcia; Flávia Guirro Zuliani; Cristiane Lara Mendes‐Chillof; Silméia Garcia Zanati Bazan; Carlos Clayton Macedo deFreitas; Gabriel Pinheiro Modolo; Vitor Mendes Pereira; Gustavo José Luvizutto; Rodrigo Bazan (Annals of the Child Neurology Society)
Abstract Background Management of pediatric stroke is challenging because of the paucity of data supporting the efficacy of interventions. This scoping review details the treatments available for the acute phase of stroke in pediatric patients with arterial ischemic stroke. Summary of Review Overall, 68 relevant articles were published between 2001 and 2023. The primary study included 48 case reports (n = 48). Eleven articles reported the use of intravenous thrombolysis (IVT) with alteplase, eight used intra‐arterial (IA) alteplase, and 52 reported mechanical thrombectomy (MT). IVT was administered to 195 patients with a median of 5.5 h of stroke onset, and only four (2.0%) had intracranial hemorrhage after alteplase treatment. Of the 11 articles, nine used 0.9 mg/kg IVT administered as a 10% bolus, with the remaining 90% administered over one hour, and one study used 0.54 mg/kg. IA was performed in 17 patients with a median of 5.05 h of stroke onset, and three individuals (17.6%) had intracranial hemorrhage. Of the eight reports that document IA, two used 0.9 mg/kg; one each used 0.16 mg/kg, 0.1 mg/kg, 0.6 mg/kg, 100 mg/day, and 10 mg/day; and one article documented the use of urokinase 750 000 IU. MT was used in 434 and 215 individuals in a previous systematic review, with a median of 11.82 h of stroke onset, and only 2.9% had intracranial hemorrhage after the treatment. Stent retrievers were used in 33 reports (63.5%) and aspiration retrievers were mentioned in 15 articles (28.8%). Overall, the outcomes ranged from complete to moderate recovery for all modalities. Conclusions IVT and MT are safer than IA; however, despite the lack of clinical trials, all modalities seem effective in improving clinical recovery. To guide clinical practice and determine better intervention modalities, clinicians should note the key messages from this review, such as using magnetic resonance imaging in the acute phase and identifying key risk factors and presenting symptoms.